OVERVIEW OF PECTIN AS AN EXCIPIENT AND ITS USE IN THE PHARMACEUTICAL DOSAGE FORM - SOPYAN, IYAN; GOZALI, DOLIH; K. S., INSAN SUNAN; GUNTINA, RIZKA KHOIRUNNISA (International Journal of Applied Pharmaceutics, 2022)
Pectin is a polysaccharide that is abundant in nature and has promising uses in the pharmaceutical field. Pectin is resistant to digestive enzymes but pectin gel can swell in aqueous media and small amounts of compounds can be released into the gastrointestinal tract. This problem can be solved by developing pectin composites obtained from the incorporation of pectin polymers with other polymers. This article discusses the interaction of pectin with other polymers in various drug delivery systems. The method used in review articles is to review nationally and internationally published scientific journals obtained from Google, Google Scholar, Pubmed and Science Direct. From several related studies, delivery systems that have been developed and reported in the form of films, hydrogels, particulate systems and tablets. Other polymers such as Alginatee, protein, chitosan, gelatin and starch are known to improve the properties of pectin so that pectin composites can be used as controlled drug delivery. Thus, the development of other drug delivery systems with pectin composites becomes an opportunity and challenge in the future.